Examining the Effects of Work-Life Balance and Supervisor Support on Turnover Intention: The Mediating Role of Job Satisfaction - David J M Nainggolan; Murtianingsih; Widi Dewi R (Al-Qalam Institue, 2026)
This study investigates the effect of work-life balance and supervisor support on turnover intention, with job satisfaction serving as a mediating variable among employees of PT PLN (Persero) Pusat Sertifikasi. Grounded in social exchange theory and organizational behavior perspectives, this research addresses employee retention issues within a state-owned enterprise context. A quantitative explanatory design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data was collected from 80 employees through structured questionnaires and analyzed using SmartPLS 3. The results demonstrate that work-life balance and supervisor support have a positive and significant effect on job satisfaction. Work-life balance also exerts a significant direct effect on turnover intention. However, supervisor support and job satisfaction do not significantly affect turnover intention. Furthermore, mediation analysis confirms that job satisfaction does not mediate the relationship between the independent variables and turnover intention. These findings indicate that turnover intention in public sector organizations is shaped not only by attitudinal factors but also by structural and organizational conditions. This study contributes to the empirical development of human resource management literature and provides managerial implications for strengthening employee retention strategies